2011
DOI: 10.1021/ie1024744
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Selected Vinylimidazolium Ionic Liquids and Their Effectiveness as Corrosion Inhibitors for Carbon Steel in Aqueous Sulfuric Acid

Abstract: Five imidazolium-type ionic liquids, containing both N1 unsaturated and N3 long alkyl saturated chains as cations and bromide as anion (IL1–IL5), were obtained by conventional and microwave synthesis. Compounds were tested in aqueous 1 M H2SO4 as corrosion inhibitors for carbon steel. Weight loss and polarization curves indicated that inhibition efficiency increased with concentration, which turns out to be dependent on alkyl chain size linked to N3 (IL4 > IL3 > IL1 > IL2 > IL5). The relatively high inhibitory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(56 citation statements)
references
References 51 publications
0
52
0
4
Order By: Relevance
“…The dissolution of Al has been reported to be more rapid in acidic solutions containing chloride or fluoride ions than in the near-neutral solutions [4][5][6]. Corrosion inhibitors offer an efficient, a convenient and relatively cheap method of controlling corrosion of metals in various aggressive media [3,[7][8][9][10][11]. For this reason, a number of studies have been reported on the use of corrosion inhibitors to mitigate the corrosion of Al in chloride solutions [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dissolution of Al has been reported to be more rapid in acidic solutions containing chloride or fluoride ions than in the near-neutral solutions [4][5][6]. Corrosion inhibitors offer an efficient, a convenient and relatively cheap method of controlling corrosion of metals in various aggressive media [3,[7][8][9][10][11]. For this reason, a number of studies have been reported on the use of corrosion inhibitors to mitigate the corrosion of Al in chloride solutions [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…
Abstract:The effects of seven macrocyclic compounds comprising four phthalocyanines (Pcs) namely 1,4,8,11,15,18,22,2,3,9,10,16,17,23,2,9,16, and 29H,31H-phthalocyanine (Pc4), and three naphthalocyanines namely 5,9,14,18,23,27,32,2,11,20, properties of the compounds were also investigated. All the studied compounds showed appreciable inhibition efficiencies, which decrease with increasing temperature from 30 °C to 70 °C.
…”
mentioning
confidence: 99%
“…There are various organic inhibitors that tend to decrease the corrosion rate of steel and iron in acidic solutions [28,[83][84][85][86]. ILs with imidazolium [87][88][89][90][91][92] and pyridinium cations [93,94] have showed excellent corrosion inhibition performance on mild steel in an acidic environment. We have irst investigated the acid corrosion inhibition process of mild steel [2] 4 .…”
Section: Mild Steelmentioning
confidence: 99%
“…They offer novel physical and chemical properties like low toxicity, high chemical stability, low vapour pressure and high electrical conductivity [152][153][154][155][156][157].…”
Section: Synthetic Compounds As Efcismentioning
confidence: 99%